High Silicon Dioxide Zeolite Modification Impact on Selectivity of Low Olefins Formation from Methanol; 39th International Petroleum Conference, Bratislava, Slovak Republic, September 20-23, 1999 : proceedings; Vol. 2 - Erofeev V. I. Vladimir Ivanovich (1999, 1999)
В фонде НТБ ТПУ отсутствует